STRATEGI PEMASARAN SARI BUAH BELIMBING UD. CEMARA SARI KARANGSARI (Studi Kasus di UD. Cemara Sari, Karangsari, Kota Blitar) - Dio Ananda, Ricky; Wahyu Budiman, Eko; Brillian Pintakami, Lintar (grafting, 2022)
This study aims to determine the marketing mix, internal and external factors and alternative product marketing strategies in UD. Spruce Sari. The results showed internal factors that influenced in terms of strength, namely using the original fruitabelimbing with a score of 0.36 and in terms of weakness, namely less vigorous promotion with a score of 0.08. The most influential external factors in terms of opportunities are cooperation with outside parties with a score of 0.27 and in terms of threats, namely new competitors with the same product with a score of 0.10. The alternative strategies that can be applied are increasing the quantity of production to maintain an increase in consumer demand during the big day, utilizing social media to find out the latest information about the market, and collaborating with out-of-town agents.